Social exclusion influences attentional bias to social information. Issue 3 (30th March 2015) - Xu, Mengsi; Li, Zhiai; Zhang, Junhua; Sun, Lijing; Fan, Lingxia; Zeng, Qinghong; Yang, Dong
<x xml:space="preserve">Abstract</x> Using three experiments, the present study investigates the impact of social exclusion on attention. Specifically, we investigate whether social exclusion promotes attentional bias to social acceptance cues (smiling faces) or social exclusion cues (angry faces) among an Asian population. The Cyberball game was adopted to manipulate social inclusion or exclusion, and a dot‐probe task was used to measure individuals' responses to smiling or angry faces. In Experiments 1 and 2, each trial consisted of either a smiling or angry face that was paired with a neutral face. In Experiment 1, when the stimulus onset‐asynchronies (SOA) were 500 ms, the inhibition of return emerged, indirectly indicating that social exclusion promotes sensitivity to social acceptance cues. In Experiment 2, after setting the SOA to 200 ms, we found that social exclusion promotes attentional bias to smiling faces compared to neutral faces. In Experiment 3, both smiling and angry faces were shown during each trial, and we found that social exclusion promotes attentional bias to smiling faces compared to angry faces. Therefore, the present study extends our understanding of the relationship between social exclusion and attention. Overall, it appears that after social exclusion, the desire for social reconnection trumps the desire to avoid social exclusion.